PENGARUH KECEPATAN DAN SUDUT POTONG TERHADAP KEKASARAN BENDA KERJA PADA MESIN BUBUT - Paridawati, Paridawati (Jurnal Ilmiah Teknik Mesin, 2015)
This study aimed to determine the extent of the influence of cutting speed and tools angle to find the best resultof roughness of the workpiece on a lathe machine. The variables used were: spindle rotation speed, anglevariation of tools (clearance angle, relief angle, rake angle, and the back rake angle), and the depth of feeds.With three variations of the speed and four variation of angular tools and twelve materials testing (ST 37), theexpected results obtained from this study are to find the best result of roughness of production standard.With three levels of speed variation and four tools angle variations already mentioned above, is expected to getresults as expected. ST 37 workpiece and cutting tool HSS (High Speed Steel) is an option in writing this essay.The final results of this study in the form of graphs and statistical data is the result of the roughness of theworkpiece ST 37 were tested using a measuring device called surface flatness tester.